Distribution and frequent occurrence of diatom taxa (Bacillariophyta) inhabiting warmer oceans in Seogwipo coast of Jeju Island, southernmost Korea - Joh, Gyeongje (Phytotaxa, 2021)
The epiphytic diatoms attached to seaweeds and benthic diatom assemblages, have been collected along the Seogwipo coast in Jeju Island, South Korea. In the last three-year survey, 80 diatom taxa inhabiting warmer oceans have been found, including those in the tropical and subtropical regions such as the Pacific Ocean, the Caribbean Sea, the western Indian Ocean, and other warmer regions. These diatom flora shows a worldwide pattern that concentrated around the Tropic of Cancer. This survey of local areas reveals the existence of many rare or retrieved taxa that were not well known until recently. Furthermore, some of them, including Aulacodiscus affinis, Leudugeria janischii, Hyalosynedra lanceolata, Trachyneis velata var. ornata, Lyrella concilians have been reported for the first time since the first entry or haven been reported only once. Of the diatom flora described here, 48 taxa are new to South Korea and previously unrecorded in the local area.